The More Religiosity, the Less Creativity Across US Counties - Okulicz-Kozaryn Adam (European Regional Science Association (ERSA), 2015)
It is not an overstatement to say that creativity is the single most important ingredient for broadly understood progress (technological, economic, social, academic, and so forth). Rapid automation makes creativity increasingly important, because non-creative tasks can and will be automated. It is striking that there are hardly any studies about the link between religiosity and creativity. Religion is a powerful and persistent force shaping human society. This study investigated the relationship between religiosity and creativity across US counties. Religiosity was measured as adherence and church density. Creativity was measured as a proportion of people in occupations classified as creative and patents per capita. Results indicate that religious counties are less creative, even controlling for education, income, political orientation, urban-rural continuum, and prevalent industry. Directions for future research are discussed
Keywords: 330